Legal consequences of execution of fiduciary collateral sold or pledged by the debtor - Jayadi Prasetya; Mochammad Nurwenda Faizal; Ana Harlina; Devi Mardianti (Magister Kenotariatan Universitas Pasundan, 2022)
The writing of this scientific work entitled